A review of the literature on the environmental impacts of marine fish cage culture (ESP) - Watts, Jennifer; E. Conklin, Douglas (Uniciencia, 1998)
A review of the literature is presented that covers current knowledge of documented environmental impacts that result from cage-culture of fish in coastal waters. Little work has been done that document these types of impacts in tropical environments therefore selected topics taken from studies on salmon net-pen culture will be briefly reviewed. The areas covered include: a) concerns related to eutrophication in coastal areas, b) information on feed utilization and waste production in salmon net-pen culture, c) the extent and nature of observed impacts on benthic communities, d) possible effects on local fish communities and e) concerns related to the use of chemicals in intensive fish culture. The development of simulation models to describe and predict impacts from coastal fish farming is discussed. Recommendations for future research are also made.